Website base document management application for PT TPS Surabaya. - taufiqurrahman, naufal as'ad; Lemantara, Julianto; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT Terminal Petikemas Surabaya (Surabaya Container Terminal/TPS) is one of PT PELINDO III subsidiaries. Its business line is in providing international container terminal facilities for trading in domestic as well as ocean goingÂ  trajectoriesin Indonesia. Its motto isÂ  â€œReliable Terminal with Service Excellenceâ€. Reliable means responsive, emphaty, learning, innovation, ability, benefit, leading, and effective. One of the motto which supports all business activities in PT TPS is responsive and innovation. It means that all TPSâ€™s services are provisedÂ  with fast and up to date computer system and equipment. Based on the identification and interview conducted in PT TPS about document management process, it was recognized that all mail document is still managed manually. It impacts on postponement of information transfer that occur inter and intra department as well as with parties outside from the company. Therefore, several problems isolated from the companyâ€™s activities are low speed distribution of mails, difficulties in mail controlling, complexity in acknowledging mail status and disposition, mail identification that needsÂ  1-3 hours, and expansion of mail storage room. Based on those description of problems, the writer suggested a technical solution that is the innovation of website base document management application for PT TPS Surabaya.